2012
DOI: 10.4143/crt.2012.44.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Consolidation Chemotherapy after Adjuvant or Primary Concurrent Chemoradiation Using Paclitaxel and Carboplatin to Treat High-Risk Early-Stage or Locally Advanced Cervical Cancer

Abstract: PurposeThis study investigated the efficacy and toxicity associated with consolidation chemotherapy using paclitaxel and carboplatin after concurrent chemoradiation (CCR) in cervical cancer patients.Materials and MethodsFrom a total of 37 patients, 19 with International Federation of Gynecology and Obstetrics (FIGO) stage IB1-IIA cervical cancer (group 1) underwent surgery followed by consolidation chemotherapy after CCR, and 18 with stage IIB-IVA disease (group 2) received consolidation chemotherapy after pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
(27 reference statements)
3
13
0
Order By: Relevance
“…So far, including ours, two studies have evaluated the efficacy of TC-based CCRT followed by consolidation chemotherapy. Kim et al [20] employed a 3 weekly schedule in stage IIB–IVA patients and reported 3-year PFS and OS rates of 51.9% and 60.0%, respectively. In contrast, although we included cases of more advanced disease (stage IIIB/IVA), we achieved better oncological outcomes; i.e., 3-year PFS and OS rates of 67.9% and 90.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, including ours, two studies have evaluated the efficacy of TC-based CCRT followed by consolidation chemotherapy. Kim et al [20] employed a 3 weekly schedule in stage IIB–IVA patients and reported 3-year PFS and OS rates of 51.9% and 60.0%, respectively. In contrast, although we included cases of more advanced disease (stage IIIB/IVA), we achieved better oncological outcomes; i.e., 3-year PFS and OS rates of 67.9% and 90.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the setting of definitive radiotherapy, although several clinical trials have been conducted [151617181920], there is limited information available regarding the efficacy and toxicity of TC-based chemoradiotherapy followed by consolidation chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…28 However, prolonged hemotoxicity may hinder the delivery of consolidation chemotherapy, especially in Chinese people. Previous studies have shown that BM requires an extended period to recover from radioactive damage after exposure to a higher dose of radiation (30Y50 Gy).…”
Section: Discussionmentioning
confidence: 99%
“…It was not determined from their study whether the effect of the chemotherapy was as a radiation sensitiser or as a systemic chemotherapy with elimination of possible micrometastasis, or both. In contrast, Kim HS et al found that consolidation chemotherapy after CCRT using paclitaxel and carboplatin failed to improve PFS and OS as compared to CCRT-only in patients with high-risk early-stage cervical cancer who underwent surgical treatment (3-year PFS, 62.7% vs. 88.2%, respectively; 3-year OS, 90.9% vs. 97.3%, respectively) [ 26 ]. However, is there any role for consolidation chemotherapy following CCRT in intermediate-risk cervical cancer patients?…”
Section: Discussionmentioning
confidence: 99%